UNDERSTANDING WITCHCRAFT AND ITS IMPLICATIONS FOR COMMUNITY DEVELOPMENT - Opuka, Enoch Harun (Impact: Journal of Transformation, 2020)
The Gospel tune “Omundu Omulosi” (meaning, “a man who practices witchcraft”) hit the charts in Kenya early in 2000 and still is popular in many radio stations today. It laments the fact that witchcraft has destroyed a home. An educated man who had just come from the United States died unexpectedly and the only cow of the family also died leaving the family poor. But is witchcraft real? And is it an impediment to the advancement of the community socially and economically? This paper uses the theory of community development as advanced by Robert Chambers which posits that “people can only support that which they help build.” The theory also continues to assert that the outsider's view of the communities is always “distorted and explained using our own language and experience.”(Chambers, 1983).The study examines witchcraft from the African perspective and its impact on community development. If the Bible is to be taken as the word of God – and if the Bible is true then as Christian we are cognizant of Paul’s exhortation in Ephesians 6:12, “For our struggle is not against flesh and blood, but against the rulers, against the authorities, against the powers of this dark world and against the spiritual forces of evil in the heavenly realms.”The questions this paper attempts to address are: Is witchcraft real or is it part of the wild imagination of the human mind? How does witchcraft impact community development? and, what can we do as Christians to counter the “forces of evil in the heavenly realms”? The paper explores literature available in order to define witchcraft arguing that witchcraft has its origin in Satanism. It also examines the phenomena of witchcraft accusations and why they are taking root in modern-day community life. In addition, the author relies on personal testimonies of people who have had encounters with this phenomenon. The paper concludes that indeed the “powers of this dark world” are still in force and that they are causing stagnation in community development in areas where witchcraft is practiced, affecting both individuals and communities. Finally, practical ways of ensuring that these powers are conquered are provided.